New Strategies in the Treatment of Ta-T1 Transitional Cell Carcinoma (TCC) of the Bladder - Maurizio A. Brausi (The Scientific World Journal)
In recent years, there have been many advances in the treatment of superficial bladder cancer. Standard intravesical chemotherapeutic agents can now be delivered more effectively thanks to new technological advances in drug delivery. Local microwave hyperthermia and electromotive drug administration are of particular interest. Research has also shown that different combinations of drugs and sequential drug delivery of two or more different drugs for differing periods of time also increase the effectiveness of possible treatments of superficial bladder cancer. Furthermore, new chemotherapeutic drugs for intravesical use are being investigated in various clinical trials, with gemcitabine showing particularly promising results. Also in the pipeline are new approaches to treatment such as gene therapy, but these will need to be developed much more before they become part of routine practice.